How to reduce workplace absenteeism - Wolter Hassink (IZA World of Labor, 2018)
Do workplace programs help reduce worker sickness absence? Many programs are based on the principle that the employee's decision to report an absence can be influenced if it is costly to be absent. Firms can reduce absenteeism by implementing broad programs, including performance pay, general improvements of working conditions, and strengthening workers' loyalty to the firm. Specific programs, such as grading partial absence, seem to be effective at reducing long-term absences. However, firms will be less inclined to implement such programs if they can shift the financial burden to social security programs.
Keywords: M5; 330; workplace sickness absence; financial incentives; working conditions